INTEGRATİNG URBAN GREEN AND CREATİVE SPACE DESİGN İN ENHANCİNG COMMUNİTY-BASED CULTURAL TOURİSM İN YOGYAKARTA - Nugroho, Martino Dwi; Nurcahyo, Mahdi; Suwahyunto, Hartoto Indra; Prasojo, Bintang; Paramytha, Pradnya; Tamimi, Shabrina; Atmojo, Muhammad Eko; Kyswantoro, Yunita Firdha (Veredas do Direito, 2026)
The development of community-based cultural tourism is a crucial strategy for sustainable urban development, particularly in a cultural city like Yogyakarta. This article aims to analyze the integration of Green and Blue Open Spaces with community-based urban creative spaces to support inclusive and sustainable cultural tourism. This study uses a qualitative approach with a case study method on the Sayidan Alley activity in Sayidan Village, Yogyakarta City. Data were obtained through field observations, documentation, and literature review. The analysis shows that the integration of open spaces with community-based creative activities can transform marginal areas into productive public spaces, strengthen local cultural identity, and encourage the growth of the community's creative economy. However, this study also identified conceptual and practical challenges, particularly related to the sustainability of spatial management, the potential for cultural commodification, and the risk of social exclusion if the tourism approach is too event- and visual-aesthetic-oriented. Therefore, this article emphasizes the importance of strengthening the role of the community as the primary actor, providing long-term institutional support, and policies that ensure spatial equity in the development of urban creative spaces. The integration of open spaces and creative spaces is positioned not only as a tourism instrument but also as a strategy for community empowerment and local cultural preservation.